Bridging Indigenous Ecological Knowledge and Digital Science Learning: A Conceptual Framework for Ethno-STEM-Based Disaster Risk Reduction Education in Indonesian Coastal Schools - Mugi Lestari; Astrid Sulistya (Research Collaboration Community (Rescollacom), 2026)
Indonesia's coastal communities face recurrent hydrometeorological and geophysical hazards, yet school-based disaster risk reduction (DRR) curricula often marginalize the ecological knowledge that indigenous communities have refined across generations. Separate bodies of research have examined the pedagogical reconstruction of indigenous knowledge into ethnoscience-based science instruction (Ethno-STEM), the cross-cultural pedagogy required for students to move between life-world and school science, and the integration of local wisdom into disaster education. However, no published framework yet unites these three strands into a single, sequenced, and ethically grounded model for developing digital ethnoscience learning modules explicitly oriented toward disaster preparedness in coastal schools. This conceptual paper addresses that gap. Drawing on a narrative synthesis of the ethnoscience, cross-cultural science education, and disaster-education literatures, the paper proposes the Ethno-STEM Digital Resilience Framework (ES-DRF), a six-stage model spanning community engagement and consent, scientific reconstruction of indigenous disaster knowledge, border-crossing curriculum mapping, ADDIE-informed digital media co-design, participatory validation, and iterative evaluation. The framework's novelty lies in embedding cross-cultural pedagogical theory and indigenous consent and benefit-sharing principles directly into the technical process of digital media development, rather than treating community consultation as a peripheral formality. As a conceptual contribution, the framework requires future empirical field validation; implications for curriculum policy, teacher preparation, and pilot studies in tsunami-, flood-, and volcanic-hazard-prone regions of Indonesia are discussed.